Low back pain: Based on Age, Working Period and Work Posture - Rachmawati, Siti; Suryadi, Iwan; Pitanola, Rizka Diajeng (KEMAS: Jurnal Kesehatan Masyarakat, 2021)
Low back pain is one of the health risks for workers. Age, years of work and work posture that are not ergonomic are associated with complaints of low back pain. This study aims to determine the relationship between age, work period, and work posture on complaints of low back pain in rice mill workers. This study used an analytical observational study, with a cross sectional approach. Samples were taken of 50 respondents using total sampling. Research instrument with a questionnaire to determine data on age, years of service and assessment of complaints of low back pain. The RULA checklist method for measuring body posture. The data analysis technique used the Pearson test and multiple linear regression. The results showed that there was a significant relationship between age, years of service and work posture with complaints of low back pain with a p value 0.05. The conclusion of this study is that there is a relationship between age, years of service and work posture with complaints of low back pain.